(untitled) (Italian Journal of Public Health, 2009)
Introduction: The Appropriateness Evaluation Protocol (AEP) is a widely used assessment tool that identifies and measures the inappropriateness variables of hospital healthcare related to unjustified admission and/or length of stay, however it does not apply specifically to gynaecology or obstetrics wards. Objectives of the study: The main objectives of the present study were to develop a new tool for the evaluation of the appropriateness of admission and hospital stay in obstetric settings; as well as to analyze the main determinants of inappropriate admission and days of hospital stay within all the units of the Pediatric Hospital “Regina Margherita” and the Obstetrics and Gynaecology Teaching Hospital “S.Anna” in Turin. Methods: A multidisciplinary team of reviewers, composed of gynaecologists, paediatricians and obstetricians, was established and the appropriateness evaluation criteria, the operational handbook and the plan were all defined. Data were collected during the period between September and December 2005 and then put in an ad hoc database. Data analysis and evaluation were performed by univariate analysis (chisquare test) and multivariate analysis using a multiple logistic regression model. The level of significance was set at p<0.05. Results: Out of 734 clinical records, 598 were considered for the study. The prevalence of inappropriateness of admission was 3.34%. The total number of examined days was 2888, 801 of which (27.74%) were considered to be inappropriate. The variables “place of residence” (÷²=6.272; p=0.0435) and “type of admission” (÷²=14.223; p<0.001) were significantly associated with the inappropriateness of the admission. Between the 2nd and the 8th day of hospital stay the percentage of inappropriate days exponentially increased (up to 56%). With regards to the quality of the clinical records almost all of them were characterized by the presence of anamnesis, objective exams, discharge letters, clinical diary entries and the signature of the responsible healthcare professional. Objective examination was often incomplete or partially complete or absent. Conclusions: The proposed Obstetric AEP was demonstrated to be useful for the evaluation of the appropriateness of obstetric admissions and hospital stays, as well as the determinants for when these were inappropriate. This specific tool, in the future, could be used to monitor hospital usage and the allocation of resources related to this health care area